GV16 acupoint stimulation with bee venom reduces peripheral hypersensitivity via activation of α2 adrenoceptors in a nitroglycerin-induced migraine mouse model - Sol-Ji Kim; Ji-Hee Yeo; Seo-Yeon Yoon; Dae-Hyun Roh (Integrative Medicine Research, 2023)
Background: Peripheral hypersensitivities develop in the face and hindpaws of mice with nitroglycerin (NTG)-induced migraine. We evaluated whether diluted bee venom (DBV) injections at acupoints prevented these peripheral hypersensitivities and c-Fos expression in the trigeminal nucleus caudalis (TNC). Methods: NTG (10 mg/kg, intraperitoneal, i.p.) was administered every other day for nine days. DBV (0.1 mg/kg) was subcutaneously injected into the ST36 (Zusanli), LI4 (Hegu), or GV16 (Fengfu) acupoints 75 min after each NTG injection. Mice were pretreated with naloxone (5 mg/kg, i.p.) or yohimbine (5 mg/kg, i.p.) 30 min before the DBV injections. Results: NTG injection caused facial cold allodynia, hindpaw mechanical allodynia, and increased c-Fos-immunoreactive (ir) cells in the TNC. Repetitive DBV injections at GV16, but not the ST36, or LI4 acupoints, suppressed NTG-induced hindpaw mechanical allodynia and facial cold allodynia. The number of c-Fos-ir cells also decreased in response to DBV injections at the GV16 acupoint. Remarkably, pretreatment with yohimbine reversed the anti-allodynic effects of DBV injections and attenuated the decreased c-Fos expression in response to GV16 DBV treatment. Naloxone did not block the effects of GV16 DBV stimulation. Conclusion: These findings demonstrate that repetitive DBV treatment at the GV16 acupoint relieves NTG-induced facial and hindpaw hypersensitivities and decreases in c-Fos expression in the TNC via activation of the alpha-2 adrenoceptors, but not the opioid receptors.